THE OF VISIONARY LEADERSHIP, DIGITAL GOVERNANCE, AND DIGITAL COMPETENCE ON EMPLOYEE PERFORMANCE THROUGH WORK EFFICIENCY AS AN INTERVENING VARIABLE IN VILLAGE GOVERNMENT IN SOOKO DISTRICT, MOJOKERTO REGENCY - Syah Putra, Rizky Daniar; Mujanah, Siti; Ardiana, I Dewa Ketut Raka (Universitas Nahdlatul Ulama Surabaya, 2025)
This study examines the influence of visionary leadership, digital governance, and digital competence on employee performance through work efficiency as an intervening variable among village government employees in Sooko District, Mojokerto Regency. The population consists of 124 employees, with a sample of 95 respondents determined using Slovin's formula. The data were analyzed using structural equation modeling (SEM) with a partial least square (PLS) approach. The findings reveal that visionary leadership big77 significantly affects employee performance but does not significantly impact work efficiency. Digital governance shows no significant effect on either employee performance or work efficiency. Conversely, digital competence significantly influences both employee performance and work efficiency. Additionally, work efficiency significantly impacts employee performance. Regarding the mediating role, work efficiency does not mediate the effects of visionary leadership or digital governance on employee performance. However, it significantly mediates the effect of digital competence on employee performance. In conclusion, digital competence and work efficiency are essential factors in improving employee performance. However, visionary leadership and digital governance require further strategic refinement to produce significant impacts. These results highlight the importance of enhancing digital competence and optimizing work efficiency to support the performance of village government employees.